2019
DOI: 10.1109/access.2019.2902122
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activity Analysis Using Higher-Order Tensor Decomposition: Application to Muscle Synergy Extraction

Abstract: Higher-order tensor decompositions have hardly been used in muscle activity analysis despite multichannel electromyography (EMG) datasets naturally occurring as multi-way structures. Here, we seek to demonstrate and discuss the potential of tensor decompositions as a framework to estimate muscle synergies from 3 rd -order EMG tensors built by stacking repetitions of multi-channel EMG for several tasks. We compare the two most widespread tensor decomposition models -Parallel Factor Analysis (PARAFAC) and Tucker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
(133 reference statements)
0
25
0
Order By: Relevance
“…A few previous studies have attempted to demonstrate the effectiveness of tensor decomposition in analyzing joint angle and EMG data [17][18][19][20][21] . In a previous study, tensor decomposition was applied to wrist EMG data, and the results demonstrated the task-dependent modulation of the spatiotemporal modules 17 . That study relied on a variant of Tucker decomposition, which is a more general type of tensor decomposition that subsumes CP decomposition.…”
mentioning
confidence: 99%
“…A few previous studies have attempted to demonstrate the effectiveness of tensor decomposition in analyzing joint angle and EMG data [17][18][19][20][21] . In a previous study, tensor decomposition was applied to wrist EMG data, and the results demonstrated the task-dependent modulation of the spatiotemporal modules 17 . That study relied on a variant of Tucker decomposition, which is a more general type of tensor decomposition that subsumes CP decomposition.…”
mentioning
confidence: 99%
“…It is implemented in the iteration phase by setting the negative values of computed components to zero by the end of each iteration to force the algorithm to converge into a non-negative solution. A similar constrained set-up have been used in previous study [15] to extract shared muscle synergies. Moreover, the algorithm would run for 10 times to ensure that the model is not converged into local minima and the decomposition with the highest explained variance is chosen.…”
Section: Constrained Tucker Decompositionmentioning
confidence: 99%
“…A few studies have attempted to demonstrate the effectiveness of tensor decomposition in analyzing the joint angle and EMG data [1719]. A previous study applied tensor decomposition to wrist EMG data and demonstrated the task-dependent modulation of the spatiotemporal module [19].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have attempted to demonstrate the effectiveness of tensor decomposition in analyzing the joint angle and EMG data [1719]. A previous study applied tensor decomposition to wrist EMG data and demonstrated the task-dependent modulation of the spatiotemporal module [19]. Despite the detailed description of mathematical and historical aspects of tensor decomposition, a description of movements and tasks is lacking; the significance of the tensor decomposition in discussing the task-dependent modulation of the spatiotemporal module is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation